Research on the Influence of Weak Interlayer in Open-Pit Slope on Stability - Zhong Shuheng; Miao Yinjun (Advances in Civil Engineering)
The weak interlayer in the slope meets with water threatening the overall stability of the slope. Sequestration location of the weak layer has an impact on the stability of the slope. Based on this, taking the south-side slope of Fushun West Open-Pit Mine as the background, the limit equilibrium method was used to study the influence of different depths and dip angles of weak interlayers on the factor-of-safety and sliding mode of the slope. After analyzing the effect, a bottom friction experiment was conducted to verify the theoretical results. The research results show that, as the buried depth of the weak layer becomes larger and the dip angle becomes smaller, the safety factor of the slope increases. Dip angle and depth both affect the sliding mode of the slope. This can provide a reference for study of the influence mechanism of weak interlayer on slope stability in multi-weak-layer slopes.